A New Design of Fuzzy Logic Control for SMES and Battery Hybrid Storage System. (May 2017) - Sun, Qixing; Xing, Dong; Yang, Qingqing; Zhang, Huiming; Patel, Jay
Abstract: In this paper, the superconducting magnetic energy storage (SMES) and battery hybrid energy storage system has been designed to deal with high fluctuating power demand due to their complementary advantage. A lot of researchers are focusing on using battery technology to deal with low frequency demand and using SMES to deal with the remaining power demand. In this paper, a new energy management control method using 3 input parameters to a fuzzy logic controller is firstly proposed to deal with high fluctuating power demands. An example data processing result is shown in this paper. The results show that the hybrid storage system which applied fuzzy logic control has more flat battery charging/discharging current than an equivalent filtration control method. The low fluctuating battery demand is ideal for extending battery lifetime. Furthermore, the fuzzy logic controller can automatically adapt to the size of the SMES system by applying the state of the charge (SOC) of SMES as an input parameter to the fuzzy logic control.